UPAYA PENGINJILAN DAN FAKTOR PENYEBAB KONVERSI AGAMA DARI HINDU KE KRISTEN PROTESTAN DI KABUPATEN BADUNG BALI - Ni Kadek Surpi (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
This psychological research aims at assessing the relationship between social identity and religious fundamentalism with the prejudice—of students at UIN Sunan Kalijaga Yogyakarta—against believers of different faiths. The research subjects of this research were 330 students of UIN Sunan Kalijaga. They had to fill in the questionnaire of three themes, namely scale of prejudice against other religions, scale of social identity, and scale of religious fundamentalism. The data is approached through regression analysis. The research found that there was no relationship between social identity and religious fundamentalism with prejudice against other religions (R = 0.114, p =0.120). This research cannot also proof the relationship between fundamentalism and prejudice against people of other faiths, as well as the relationship between social identity and the prejudice against people of other faiths.